Prophetic ministry in Poland. Spiritual encounters among Charismatics - Berdowicz, Ewelina (Humaniora. Czasopismo Internetowe, 2022)
The growth of prophetic ministry, which started in the 1980s, has resulted in numerous testimonies of great faith and hope. The emphasis put on signs and wonders, eagerly promoted by John Wimber and his adherents, has contributed to the rapid spread of new forms of worship. For decades, spiritual encounters — a desirable product in the religious marketplace, have also served as an easily recognizable trademark of both Pentecostals and Charismatics. The principal objective of the study is to investigate the nature of the prophecies shared among the selected Polish religious communities. For this particular reason, the main features of the Charismatic ritual language will be discussed, with special attention given to the question of God-Human intimacy. Furthermore, a reference will be made to the rise of the prophetic office within contemporary denominational and non-denominational churches. Finally, the content of the chosen prophecies will be thoroughly analyzed.